Association between clinical characteristics of patients with pressure ulcer in the COVID-19 pandemic - Taline Bavaresco; Dóris Baratz Menegon; Andréia Barcellos Teixeira Macedo; Raquel Yurika Tanaka; Angela Enderle Candaten (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To analyze the associations between the clinical characteristics of patients hospitalized with pressure injuries (PI) during the COVID-19 pandemic. Method: Cross-sectional study of 237 PI notifications in a hospital in southern Brazil. Collection took place in 2021 in an institutional management program, with interlocution to the patient's medical record. Analysis using descriptive statistics, Student's t-test, Pearson's chi-square and Wilcoxon. Results: The mean age was 59.4±14.4 years, with 59.7% male, 74.7% diagnosed with COVID-19. High risk (57.8%), stage 2 (80.2%), sacral region, intergluteal/gluteal region (73.0%) were predominant and death was the prevalent outcome (51.1%), with a median of 9.5 (0-217) days after notification. There was no association of death with diabetes, systemic arterial hypertension, smoking and reason for hospitalization. Conclusion: The association between the clinical characteristics of hospitalized patients with pressure injuries reflects the systemic inflammation of patients affected by COVID-19.